2007
DOI: 10.1099/vir.0.81890-0
|View full text |Cite
|
Sign up to set email alerts
|

Brains and peripheral blood mononuclear cells of multiple sclerosis (MS) patients hyperexpress MS-associated retrovirus/HERV-W endogenous retrovirus, but not Human herpesvirus 6

Abstract: Multiple sclerosis (MS)-associated retrovirus (MSRV)/HERV-W (human endogenous retrovirus W)and Human herpesvirus 6 (HHV-6) are the two most studied (and discussed) viruses as environmental co-factors that trigger MS immunopathological phenomena. Autopsied brain tissues from MS patients and controls and peripheral blood mononuclear cells (PBMCs) were analysed. Quantitative RT-PCR and PCR with primers specific for MSRV/HERV-W env and pol and HHV-6 U94/rep and DNA-pol were used to determine virus copy numbers. Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
179
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(192 citation statements)
references
References 54 publications
(94 reference statements)
12
179
0
1
Order By: Relevance
“…Several studies have demonstrated links between the expression of MSRV-Env and multiple sclerosis (MS); in particular immunohistochemical analyses of post-mortem brain tissue from MS patients localize the MSRV-Env protein to MS plaques with a higher level of protein expression in active plaques compared to inactive plaques (Mameli et al, 2007;Perron et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated links between the expression of MSRV-Env and multiple sclerosis (MS); in particular immunohistochemical analyses of post-mortem brain tissue from MS patients localize the MSRV-Env protein to MS plaques with a higher level of protein expression in active plaques compared to inactive plaques (Mameli et al, 2007;Perron et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Most significantly expression of syncytin-1 has also been shown to suppress staurosporin-induced apoptosis in Chinese hamster ovary (CHO) cells (45) Although there is significant evidence for syncytin-1 conferring a growth/survival advantage in malignant cells, there is also evidence that its expression induces demyelination and cell death in oligodendrocytes which is consistent with the protein playing a causative role in neurodegenerative disease (48). Indeed, as previously mentioned, syncytin-1 is thought to play an instrumental role in MS (30,32,49). Thus it is significant that AgNPs are also known to cause neuronal damage (50,51) and we speculate this could be augmented by induction of syncytin-1.…”
Section: Discussionmentioning
confidence: 52%
“…The reason for this is that syncytin-1 is known to be up-regulated in multiple sclerosis (30)(31)(32) and a variety of cancers (33,34), including lymphoma and leukaemia (35). It is also known to promote the fusion of malignant cells, both to themselves and normal endothelial cells which contributes to enhanced genetic instability (15,16,34) and recent work has shown that mutations in the HERV-W genomic 3'-long terminal repeat induce up-regulation of syncytin-1 expression in urothelial cell carcinoma (36).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 4 were classified as A-quality studies. 32,58,76,78 Blumberg et al 78 presented the results as high and low values of HHV-6 DNA.…”
Section: Brain Pcr/immunohistochemistrymentioning
confidence: 99%
“…Another 2 studies were classified as A quality without reaching statistical significance. 39,58 Of the studies classified as B quality, 1 study reached statistical significance, 44 whereas 8 studies did not. 23,47,[59][60][61][62]67,68 In most B-quality studies, a greater proportion of MS patients had detectable HHV-6 DNA in their PBMCs than controls; however, the results were not statistically signifi-For personal use.…”
Section: Polymerase Chain Reaction Techniquesmentioning
confidence: 99%